Gespensterjäger auf eisiger Spur - Funke, Cornelia 1958- (Loewe, 2005)
A timid boy named Tom reluctantly agrees to help professional ghostbuster Hetty Hyssop dispel an IRG (Incredibly Revolting Ghost) from an old house.
Keywords: Ghost stories; Ghosts -- Fiction; Haunted houses -- Fiction.; Haunted houses -- Juvenile fiction; Humorous stories; Gespenst; Kinderbuch